Evaluation of follicular growth and tissue viability in vitrified/warmed domestic dog ovaries after in vitro culture - Ackermann, C. L. [UNESP]; Asa, C. S.; Krisher, R.; Bauman, K.; Casey, S.; Lopes, M. D. [UNESP] (Wiley, 2017)
Cryopreservation of gametes is an important tool to preserve fertility, but for most species, including domestic dogs, data regarding ovarian tissue cryopreservation are limited. We aimed to evaluate the follicular and tissue viability and follicular growth after in vitro culture of domestic dog ovarian cortical slices cryopreserved by vitrification. Ovarian cortex was obtained from ten pairs of ovaries from domestic dogs using two methods (A and B), one for each ovary from the same bitch. At least four slices for each method were obtained from each ovary, one was processed for histology and the other three were vitrified. When the vitrified slices were warmed, one slice from each method was processed for histology and the remaining two slices were cultured in vitro for 7 days, after which they were processed for histological evaluation. Density of follicles in fresh samples was similar for both methods. For Method A, density of secondary follicles decreased, while the density of primordial follicles was maintained throughout the process. For Method B, density of primary follicles decreased after 7 days of incubation, but density of secondary follicles increased, confirming follicular growth in Method B. Overall, there were no differences between Methods A and B in follicular integrity after incubation. Fresh samples showed better arterial, venous and follicle preservation, followed by vitrified–warmed samples, but no differences were observed between methods. In conclusion, the methodology used to isolate the ovarian cortex may affect tissue and follicle viability as well as follicular development during in vitro culture.
Keywords: cryopreservation; Mexican gray wolves; ovarian slice; ovary